The Exploitation Of Innovative Eco-product Design Capabilities For Firms’ Sustainable Competitive Advantage And Sustainability Performance In The Circular Economy: The Role Of Customer Involvement - Lin, Soh Keng (2021)
The linear economy causes resource depletion, emissions and environmental degradation and respectively induces price spirals, pollution and climate change. This research considered factors which could instead reveal the benefits of the circular economy. It specifically hypothesized the exploitation of innovative eco-product design capabilities and customer involvement (the moderator) as exogenous variables influencing sustainable competitive advantage (SCA) and consequently sustainability performance - environmental, economic and social. The research model is grounded in Resource-based View (the primary theory) and supplemented with the Theory of Absorptive Capacity. Data was collected over a 12-week period using an online Google form questionnaire survey from firms of the FMM Directory 2020 with stratified sampling. A final total of 1416 emails attracted 249 responses (17.58%). These 249 responses (100%) comprised 16 (6.42%) which failed the inclusive criteria from the Food sector, 17 (6.83%) straight lines and finally 216 (86.75%) usable. The methodology used was Partial Least Squares-Structural Equation Modelling (PLS-SEM) deploying the SmartPLS v3.3.2 and IBM SPSS v26 software. Major tests included descriptive statistics, exploratory factor analysis, reflective measurement model and structural measurement model measurement. The results show all 8 hypotheses have positive relationships and are supported